Malaysia's mother of all elections : a turning point? - Yang Razali Kassim (2013)
This Malaysian general elections will be the most critical battle for power between the ruling coalition and the opposition. Much is at stake: from the future of Malaysian politics to the future of two leaders - Prime Minister Najib Razak and opposition chief Anwar Ibrahim. What will GE13 lead to?